MIXED PRESENTATION OF DIABETIC KETOACIDOSIS AND HYPEROSMOLAR HYPERGLYCEMIC STATE IN ELDERLY PATIENT AND RURAL AREA: A CASE REPORT - Waaf, Afiyfah Kiysa; Sekardira, Raesita Aliefa; Agmar , Syahroni Yudistian (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE The mixed presentation of diabetic ketoacidosis (DKA) and hyperosmolar hyperglycemic state (HHS) portends a worse prognosis and poses a unique challenge in the management of the acute complications of diabetes mellitus. We present a referred case of a 72-year-old Indonesian female, with uncontrolled diabetes mellitus and hypertension, seen with decreased consciousness, Kussmaul breathing, tachycardia, and a one-week history of productive cough. Additional examination revealed extreme hyperglycemia, severe metabolic acidosis, ketonuria, and hyperosmolar state which showed a mixed presentation of DKA and HHS. The patient’s condition was precipitated by pneumonia and complicated by the presentation of severe hyperkalemia. The patient was inadequately managed in the previous healthcare facility, but after fluid rehydration, insulin therapy, hyperkalemia, and acidosis management, and close monitoring of the patient in intensive care, the condition of the patient improved. This report emphasizes the importance of early recognition and prompt treatment of DKA and HHS in limited healthcare settings with special consideration for the elderly population.